MARCOS, A. y PÉREZ MARCOS, M. (2018), Meditación de la naturaleza humana. Madrid: Biblioteca de Autores Cristianos, 393 pp. - Acosta Lopez, Miguel Andres (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: MARCOS, A. y PÉREZ MARCOS, M. (2018), Meditación de la naturaleza humana. Madrid: Biblioteca de Autores Cristianos.